2016
DOI: 10.1111/jam.13048
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and proposed action mechanism of a new class of synthetic tricyclic flavonoids

Abstract: Based on the strong antimicrobial activity observed, this new tricyclic flavonoid has a good potential for the design of new antimicrobial agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 29 publications
1
48
1
Order By: Relevance
“…Developing novel, potent, and unique antibacterial drugs is important to overcome bacterial resistance and increase effectiveness of therapies. Many researchers reported that new derivatives of flavonoids were more active than natural flavonoids against bacteria strains (Table ; Babii et al, ). For evaluation of the antibacterial activity of hybrids of chalcones and oxazolidinones, N‐{3‐[3‐fluoro‐4‐(3‐pyridin‐2‐yl‐acryloyl)‐phenyl]‐2‐oxo‐oxazolidin‐5‐ylmethyl}‐acetamide ( 126 ; containing both chalcone and oxazolidinone moieties) was synthesized and showed potent activity toward S .…”
Section: Synthetic Derivatives Of Flavonoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Developing novel, potent, and unique antibacterial drugs is important to overcome bacterial resistance and increase effectiveness of therapies. Many researchers reported that new derivatives of flavonoids were more active than natural flavonoids against bacteria strains (Table ; Babii et al, ). For evaluation of the antibacterial activity of hybrids of chalcones and oxazolidinones, N‐{3‐[3‐fluoro‐4‐(3‐pyridin‐2‐yl‐acryloyl)‐phenyl]‐2‐oxo‐oxazolidin‐5‐ylmethyl}‐acetamide ( 126 ; containing both chalcone and oxazolidinone moieties) was synthesized and showed potent activity toward S .…”
Section: Synthetic Derivatives Of Flavonoidsmentioning
confidence: 99%
“…aureus and E . coli with MIC values of 0.24 and 3.9 μg/ml, respectively (Babii et al, ). 2,3‐Dibromo‐1,3‐diphenylpropan‐1‐one derivative ( 154 ) with two Br substitution at the positions α and β (the synthetic chalcone derivatives) possessed antibacterial activity against S .…”
Section: Synthetic Derivatives Of Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…To a certain extent, in our study, aggregation of E. faecalis V583, may protect the bacteria from SP, but conversely in some cases aggregation/agglutination of bacteria is also known to be inherent of the mechanism of action of some antimicrobial peptides [28, 29]. In addition, aggregation of bacteria is often associated with hydrophobicity, and these two parameters can help to adhere to different surfaces including intestinal epithelial cells [30].…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies on (1,3-dithiolium-2-yl)phenolates systems revealed that 1,3-dithiolium cations can act as acceptor groups in intramolecular charge-transfer processes [26,30,46,47]. Moreover, this type of compounds has been found to exhibit biological activity, in a particular case, against gram-positive and gram-negative bacteria [48][49][50][51][52][53][54][55][56][57][58]. Dithiolium systems are known for their reactivity at the C(2) -position towards nucleophiles [28].…”
mentioning
confidence: 99%